Characterizing cognitive inhibitory deficits in mild cognitive impairment. (May 2017) - Borella, Erika; Carretti, Barbara; Mitolo, Micaela; Zavagnin, Michela; Caffarra, Paolo; Mammarella, Nicola; Fairfield, Beth; Gamboz, Nadia; Piras, Federica
Abstract: Individuals with mild cognitive impairment -MCI- show relative weaknesses in executive functioning (EF), as well as poor memory, but the inhibition-related mechanisms behind EF impairment in MCI have not been examined systematically. The aim of the present study was to systematically investigate inhibitory function in individuals with MCI to ascertain whether pathological aging is characterized by deficits in inhibitory processes and whether such impairment is confined to specific inhibition-related mechanisms. Tasks assessing inhibition-related functions – i.e. prepotent response inhibition (measured with the Color Stroop test), response to distracters (assessed using a text with distracters task), and resistance to proactive interference (assessed with a proactive interference task) – were administered to individuals with MCI and to healthy older controls. Individuals with MCI made more intrusion errors in the proactive interference task than controls, while the two groups' performance was comparable in prepotent response inhibition and response to distracters. This pattern of findings suggests that MCI is associated with specific inhibition problems.ty Highlights: Inhibition deficits in individuals with mild cognitive impairment (MCI) are not consistently reported. The different dimensions of cognitive inhibition in MCI were examined. MCI is associated with specific rather than general inhibition problems. MCI are more susceptible to proactive interference.